First record and distribution extension of two emperor fishes, Lethrinus semicinctus and Lethrinus olivaceus to the East Coast of Peninsular Malaysia - Siti Asmal Mat Piah,; Hui, Hui Lee; Nur Athirah Abd Latiff,; Li, Lian Wong; Okamoto, Jo; Motomura, Hiroyuki; Kimura, Seishi; Ying, Giat Seah (Universiti Kebangsaan Malaysia, 2023)
This study reports the occurrence of two species of Lethrinus (family Lethrinidae) on the east coast of Peninsular Malaysia. The specimens were caught by commercial bottom trawlers operating in the southern part of the South China Sea and landed at several fish landing ports. Lethrinus semicinctus Valenciennes, 1830 and Lethrinus olivaceus Valenciennes, 1830, previously known from Borneo, with the latter also occurring in the Straits of Malacca on the west coast of Peninsular Malaysia, are now documented as new records of geographic range in the northeastern coast of Peninsular Malaysia. These records add to published Malaysian literature with photographic records, locality details, collection numbers and preserved specimens. Diagnostic characters for both species are given, as well as detailed morphometric and meristic data.